Rotavirus in Water Environments: A Systematic Review and Meta-Analysis - Aaron Awere-Duodu; Eric S Donkor (Environmental Health Insights)
Background: Despite the adoption of rotavirus vaccines, sporadic outbreaks of the virus have been reported in many parts of the world. These outbreaks are facilitated by several factors including the ease of transmission of rotavirus through water environments. This systematic review aimed to determine the global prevalence of rotavirus in water environments. Methodology: Comprehensive Boolean searches were conducted in PubMed, SCOPUS, and Web of Science. A total of 75 eligible studies were included in the study, from which data was extracted for both systematic review and meta-analysis. Extracted prevalence data was grouped according to six water categories: drinking water, untreated sewage, treated sewage, surface water, groundwater, and others. A single-group prevalence meta-analysis was conducted in RStudio version 4.3.3 subjecting the data to the random-effects model. Results: The included studies were conducted in 32 countries that span 5 continents: Africa, Asia, Europe, North America, and South America. The pooled prevalence of rotavirus in water environments was 40.86%. Among the individual water environments, untreated sewage had the highest prevalence (68.27%), followed by treated sewage (53.07%), surface water (33.40%), groundwater (25.64%) and drinking water (9.46%). Continental stratification of the prevalence data was as follows: Africa (51.75%), Asia (32.48%), Europe (55.90%), North America (41.80%), and South America (28.51%). Conclusion: There is a high prevalence of rotavirus in water environments, especially in untreated sewage, and in Europe. Further research is needed to find more efficient methods that can effectively eliminate rotavirus to insignificant levels in water environments.